ANALYSIS OF GOODS RECEIPT PROCEDURES ON INVENTORY RECORDING COMPLIANCE AT HOTEL X BOGOR - Jessica Elvira Thanos; Siti Nuraini; Riski Putrikusumaningsih (Finance : International Journal of Management Finance, 2024)
This study analyzes the implementation and compliance of Standard Operating Procedures (SOPs) in the goods receiving and requisition processes at Hotel X Bogor. The increasing operational demands in the hospitality industry require effective inventory and logistics management to ensure cost efficiency and service quality. This research uses a qualitative descriptive method with purposive sampling, where data were gathered through observations, interviews, and documentation. The analysis process includes data reduction, data presentation, and verification. The findings indicate that the goods receiving SOP at Hotel X is aligned with industry standards, covering document verification, quantity and price checks, classification of inventory items, special handling procedures for perishable goods, and daily reporting to the cost control division. The requisition SOP includes strict warehouse operating hours, the implementation of the First In First Out (FIFO) system, daily documentation of item requests, planning for imported goods' lead time, and monthly physical inventory checks. Flowchart analysis shows that both SOPs are integrated with the hotel’s information system (Power Pro), enabling accurate and efficient data processing. Overall, the SOPs are well-structured and support effective internal control, although improvements in digitalization and system integration could further enhance operational performance.